A method based on environmental monitoring and building dynamic simulation to assess indoor climate control strategies in the preventive conservation within historical buildings. (21st October 2019) - Frasca, Francesca; Cornaro, Cristina; Siani, Anna Maria
Abstract : This paper proposes a multidisciplinary method to provide improved conservation strategy and thermal comfort for visitors in historical buildings. The method combines microclimate observations along with the dynamic simulation of the building and an empirical evaluation of the degradation of hygrosocopic artifacts. It was applied to a historic building in Priverno (Italy) where cracks along the tangential direction in valuable wooden ceilings were observed. The method produced an identification strategy for temperature control that, if applied, would reduce the total size of cracks from 0.25 mm to 0.10 mm.